Empire and Religion in the Roman World - Flower, Harriet I. (University of Cambridge ESOL Examinations, 2021)
Cutting-edge essays from distinguished scholars exploring key facets of the Roman Empire. Three major themes prevail: the interaction between boundaries and intricate networks of connections; the ways in which the Roman world promoted religious change, especially the rise of Christianity; and the violence endemic within and beyond communities